English for IT 2 = Tiếng anh chuyên ngành Công nghệ thông tin 2 - Nguyễn Hằng Phương (Trường Đại học Thuỷ Lợi, 2020)
Nội dung bài giảng bao gồm: Unit 7: The Web + Web design; Unit 8: Internet security; Unit 9: Graphics and design; Unit 10: Multimedia; Unit 11: Program design and computer languages; Unit 12: Jobs in ICT; Unit 13: Communication systems; Unit 14: New technologies